Stress, Appraisal, Coping and Adaptation of Family Caregivers of Patients on Dialysis: A Transactional Theory Approach - Tudayan-Espiritu , Claire (Journal of Interdisciplinary Perspectives, 2024)
The primary purpose of this research was to determine the levels of stress, appraisal, coping, and adaptation among family caregivers. The study employed a quantitative descriptive research design. There were 402 respondents involved in this study who completed a survey questionnaire. The results demonstrated that family caregivers experienced moderate stress levels, yet exhibited exceptional levels of appraisal, coping, and adaptation. The data analysis led to the conclusion that family caregivers of dialysis patients face stressors, including financial burden, but cope well. They feel supported, satisfied, and in control of their caregiving experiences. They also manage their responsibilities well by adjusting to their work, social life, and finances, and prioritizing patient care. To address these findings, the researcher recommends that healthcare providers establish tailored stress management and counseling programs to support family caregivers of dialysis patients. By providing such resources, healthcare providers can help caregivers manage the range of stressors they face on a daily basis. Furthermore, social workers should continue offering emotional support and resources to caregivers, which will help maintain their positive appraisal and sense of control over their caregiving experiences. Empowering family caregivers in this way can help them feel better equipped to tackle the challenges that come with caring for their loved ones.